The mediating role of health awareness in the relationship between health information behavior and health outcomes among the older adults - Li, Hong; Shi, Li; Xing, Ya-Long (Frontiers in Public Health, 2025)
BackgroundWith global population aging, older adults face challenges in obtaining, understanding, and applying health information, which are critical for effective health management. Drawing on the Health Belief Model (HBM), this study examines how health information acquisition, understanding, and application influence older adults’ health awareness and, in turn, their health outcomes, with health awareness as a mediator.MethodsA structured questionnaire measured three health information behaviors (acquisition, understanding, application), health awareness, and self-reported health outcomes in a representative sample of community-dwelling older adults. Structural Equation Modeling (SEM) tested direct and indirect pathways linking these variables.ResultsSEM revealed significant direct effects of health information behaviors on awareness: acquisition (β = 0.88, p < 0.001), understanding (β = 0.83, p < 0.001), and application (β = 0.94, p < 0.001). Health awareness then strongly predicted health outcomes (β = 0.93, p < 0.001). In single-factor mediation models, awareness significantly mediated the effects of acquisition and application on outcomes but not understanding. In the full model, acquisition and application maintained significant paths to awareness (β = 0.88 and 0.94, respectively; p < 0.001), whereas understanding did not (β = 0.05, p = 0.188). Indirect effects via awareness were largest for acquisition (0.58, p < 0.001), followed by understanding (0.53, p < 0.01) and application (0.29, p < 0.001).ConclusionWhile all three information behaviors enhance health awareness, application and acquisition are most influential. Health awareness significantly mediates how acquisition and application translate into improved health outcomes. Public health strategies should therefore emphasize not only access to and comprehension of health information but, critically, its practical application through tailored digital platforms and community education.